2003
DOI: 10.1016/s0304-3959(03)00116-7
|View full text |Cite
|
Sign up to set email alerts
|

Pain and uterine contractions during breast feeding in the immediate post-partum period increase with parity

Abstract: Previous research has shown that post-partum abdominal pain is greater in multiparous than primiparous women (Murray and Holdcroft, 1989). Although breast feeding in the immediate post-partum period induces uterine contractions and abdominal pain, it is unknown how parity influences the contractions. Here, a structured questionnaire that included the McGill Pain Questionnaire (total pain intensity index, TPI) and visual analog scales (VAS) was used to evaluate the intensity, location, referred tenderness (hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 27 publications
1
57
1
8
Order By: Relevance
“…We also found that breastfeeding tended to exacerbate postpartum pain and that increased postpartum pain can influence the mothers to avoid breastfeeding immediately after birth. A study in England demonstrated that perceived pain during breastfeeding increases with parity due to stronger contractions 18 . Pain is a multidimensional experience with physiological, psychological and social components, and the pain of childbirth is rated as one of the most intense of all pains, but it is also extremely variable 11 .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that breastfeeding tended to exacerbate postpartum pain and that increased postpartum pain can influence the mothers to avoid breastfeeding immediately after birth. A study in England demonstrated that perceived pain during breastfeeding increases with parity due to stronger contractions 18 . Pain is a multidimensional experience with physiological, psychological and social components, and the pain of childbirth is rated as one of the most intense of all pains, but it is also extremely variable 11 .…”
Section: Discussionmentioning
confidence: 99%
“…31 Subsequently, infants received usual care from their individual physicians. To assess compliance with assigned randomization group, and assess when mature milk production began, a research assistant called mothers daily using a previously validated technique.…”
Section: Methodsmentioning
confidence: 99%
“…Reproductive history also may be important to document. For example, pain during breastfeeding in the first week postpartum is directly predicted by parity, with women who have given birth to more children experiencing more pain [87]. Conversely, in the laboratory (and not in close proximity to birth), multiparous women have higher pain thresholds than nulliparous women [82].…”
mentioning
confidence: 99%